2014
DOI: 10.3389/fnhum.2014.00518
|View full text |Cite
|
Sign up to set email alerts
|

Single motor unit firing rate after stroke is higher on the less-affected side during stable low-level voluntary contractions

Abstract: Muscle weakness is the most common outcome after stroke and a leading cause of adult-acquired motor disability. Single motor unit properties provide insight into the mechanisms of post-stroke motor impairment. Motor units on the more-affected side are reported to have lower peak firing rates, reduced discharge variability and a more compressed dynamic range than healthy subjects. The activity of 169 motor units was discriminated from surface electromyography in 28 stroke patients during sustained voluntary con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 80 publications
(125 reference statements)
4
23
0
Order By: Relevance
“…A decrease of MUNE in the FDI muscle indicates less number of motor units being recruited which leads to reduced maximal strength. Other factors such as decrease of motor unit firing rates can also account for muscle weakness [32, 3739]. …”
Section: Discussionmentioning
confidence: 99%
“…A decrease of MUNE in the FDI muscle indicates less number of motor units being recruited which leads to reduced maximal strength. Other factors such as decrease of motor unit firing rates can also account for muscle weakness [32, 3739]. …”
Section: Discussionmentioning
confidence: 99%
“…This muscle weakness post-stroke has been attributed to alterations in the descending voluntary command, and to anatomical and physiological changes within the muscle ( McComas et al, 1971 ; Bourbonnais and Noven, 1989 ; Dattola et al, 1993 ). Previous studies have identified impairments in voluntary muscle activation ( Riley and Bilodeau, 2002 ; Knorr et al, 2011 ; Bowden et al, 2014 ; Hoffmann et al, 2016 ), altered motor unit (MU) firing rates ( Rosenfalck and Andreassen, 1980 ; McNulty et al, 2014 ), a reduced ability to modulate MU firing ( Gemperline et al, 1995 ; Mottram et al, 2014 ; Li et al, 2015 ) and abnormal MU recruitment patterns ( Tang and Rymer, 1981 ; Hu et al, 2015 , 2016 ), all of which may contribute to muscle weakness post-stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Garland et al (2014) reviewed stroke-related changes in motor unit discharge characteristics and suggested that residual motor control strategies may remain after stroke. McNulty et al (2014) investigated motor unit firing characteristics in different muscles of stroke survivors showing that the effects on peak firing rates and their dynamic range differ not only between joints of the upper and lower limbs but also between muscles of different joints of the same limbs. Furthermore, they have shown that motor units on both paretic and non-paretic sides changed after stroke.…”
mentioning
confidence: 99%